PENGARUH SENAM LANSIA TERHADAP PENURUNAN TINGKAT NYERI PUNGGUNG BAWAH PADA LANSIA DI PUSKESMAS HELVETIA MEDAN - Johani Dewita Nasution (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2016)
Elderly gymnastic is a movement with the regular rhythm, directed and planned followed by the elderly in order to increase the physical functional. This research aims to study the influence of the elderly gymnastic to the lower back pain to the elderly at the Puskesmas Helvetia Medan. This research is Quasy Experimental design using Pretest-Posttest Design in which this research was conducted by initial observation (pretest) before intervention. The number of population in this research is 95 persons of elderly. The sample is determined by accidental sampling. The result of research indicates that before the elderly gymnastic, the lower back pain in medium level is for 26 respondents (100%) and after the elder gymnastic, the number of respondent with the medium lower back pain is 15 respondents (57.7%). The result of statistical test it indicates the significant result to the minimization of the lower back pain with P = 0.000 (P<0.005). Based on this ressults it conclude that the elder gymnastic influence the minimization of the lower back pain to the elderly. It is suggested to the health service to provide the elderly with gymnastic that can minimize the lower back pain to the elderly